Pengaruh pendekatan permainan mengajar dalam proses pembelajaran senam untuk meningkatkan roll forward - Handayani, Sri Gusti; Komaini, Anton; Callixte, Cyuzuzo; Lesmana, Heru Syarli; Jr, Procopio B. Dafun (Universitas Nusantara PGRI Kediri, 2023)
This study aims to analyze the effectiveness of the gymnastic learning model, which makes students more active during learning to improve students rolling skills. This type of research is an experiment with a pre and post-test design. 34 people with an average age of 15 years, consisting of 16 men and 18 women, participated in this study. Subjects were divided into two groups the experimental and control groups. They were taking research subjects using a purposive sampling technique. The control group carried out an independent study according to the instructions from the teacher, while the experimental group was treated with a play learning model according to the treatment program that had been made in each lesson. The forward roll skill test instrument uses a forward roll skill test sheet which contains a forward roll assessment indicator, which consists of 10 assessment indicators, starting from the initial phase, the primary phase, and the final phase for the forward roll movement. Data analysis was performed using the SPSS application with the Paired t-test method. This study's results reported a significant difference in the experimental group (p<0.05) compared to the control group. Each group has an average difference so that the learning model applied can improve forward-rolling skills in gymnastic materials.